PENGARUH STUDENT TEAMS ACHIEVEMENT DIVISION BERBANTUAN DOMINO-CHEM TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA - Rachmawati, Fitriyani Ikka; Sahputra, Rachmat; Rasmawan, Rahmat (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractPurpose of this research was to determine either able or no the differences in motivation and learning outcomes between students taught by STAD assisted learning model domino chem and conventional in class X in SMA PGRI 1 Pontianak on ion bonding and to determine how much influence the use of STAD learning model assisted by Domino chem to students learning outcomes. This research was quasi experiment with "Nonequivalent control group design". Sampling technique used saturated sampling technique. Measurement technique as collecting data technique. Motivation learning questionnaire and learning outcomes test as data collecting tools. Motivation hypothesis test used U-Mann Whitney yields Asymp value. sig. (2-tailed) of 0.113> 0.05 so that Ha is rejected (Ho accepted), there was no difference of learning motivation of control class student and experiment class. Hypothesis test of learning result used U-Mann Whitney test yield Asymp value. sig. (2-tailed) of 0.004 <0.05 so that Ho is rejected (Ha accepted), this mean that there were the differences in the students' learning outcomes of the control class and the experimental class. The learning model of STAD-aided Domino-chem gave a high influence on learning outcome of 1.09.Keywords: Domino-chem, motivasi, ikatan ion, STAD